2018
DOI: 10.1155/2018/2984730
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Approach to Understand the Association of DNA Repair with Longevity and Healthy Aging Using Genomic Databases of Oldest‐Old Population

Abstract: Aged population is increasing worldwide due to the aging process that is inevitable. Accordingly, longevity and healthy aging have been spotlighted to promote social contribution of aged population. Many studies in the past few decades have reported the process of aging and longevity, emphasizing the importance of maintaining genomic stability in exceptionally long-lived population. Underlying reason of longevity remains unclear due to its complexity involving multiple factors. With advances in sequencing tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 144 publications
0
5
0
Order By: Relevance
“…Accordingly, several years ago Vijg and Suh suggested that longevity might be related to genomic integrity. The relatively low level of chromosomal aberrations observed in older persons should be a consequence of their genomic stability, and hence, a contributing factor to their attainment of advanced age [ 65 ]. The evidence for this is largely based on accelerated aging phenotypes of DNA repair in mice mutants and human progeroid syndromes [ 66 , 67 ].…”
Section: Genes Shown To Be Associated With Longevitymentioning
confidence: 99%
“…Accordingly, several years ago Vijg and Suh suggested that longevity might be related to genomic integrity. The relatively low level of chromosomal aberrations observed in older persons should be a consequence of their genomic stability, and hence, a contributing factor to their attainment of advanced age [ 65 ]. The evidence for this is largely based on accelerated aging phenotypes of DNA repair in mice mutants and human progeroid syndromes [ 66 , 67 ].…”
Section: Genes Shown To Be Associated With Longevitymentioning
confidence: 99%
“…Additionally, studies conducted on centenarians and long-lived species highlight that genome stability and proper DNA repair mechanisms are essential for achieving a prolonged lifespan (Keane et al, 2015;Y. J. Kim et al, 2018;Simon et al, 2022;.…”
Section: Genomic Instabilitymentioning
confidence: 99%
“…In this context, genomic instability is considered a primary feature of aging that subsequently affects a cascade of age‐associated imbalances related to the epigenome, cellular senescence, stem cells, and telomeres (Schumacher et al., 2021). Additionally, studies conducted on centenarians and long‐lived species highlight that genome stability and proper DNA repair mechanisms are essential for achieving a prolonged lifespan (Keane et al., 2015; Y. J. Kim et al., 2018; Simon et al., 2022; X. Tian et al., 2019).…”
Section: “Old” Hallmarks Of Aging—longevity Perspectivementioning
confidence: 99%
“…For the quantification, metabolites or proteins can be determined through control diseases individual's samples. In this analysis, the blood samples are very much potent as obsolete biomarkers for age-related disorders [10,11]. In several reports it was noted that due to progression of age, disorders like cancer, stroke, cardiovascular diseases etc., are impede in the aged individuals as compared to the younger individuals [9].…”
Section: Role Of Proteomics and Metabolomics As Biomarkersmentioning
confidence: 99%